Branching out: Consequences of the dispersion of authoritarian elites across state and government in Latin America. Issue 3 (3rd April 2021) - Albertus, Michael; Deming, Mark
ABSTRACT: Authoritarian-era elites often do not quietly withdraw from political life after democratic transitions. Recent scholarship shows how elites can often perpetuate their influence under democracy through authoritarian successor parties. But what are the implications for the quality of democracy when former authoritarian elites lack visible formal organization under democracy yet manage to obtain a wide range of influential positions across government? We begin to answer this question using original data on authoritarian-era elites and their official positions under Latin American democracy from 1900 to 2010. We find that former authoritarian elites' access to influential posts across state and government institutions per se matters for the overall quality of democracy, regardless of whether elites are organized in an authoritarian successor party or democracy operates under holdover authoritarian institutions. This finding is an important corrective to the prevailing notion that the survival of authoritarian-era elite individuals after democratic transition hinges on the survival of authoritarian-era parties. Elites may be broadly dispersed across parties under democracy, but their influence is undiluted when they are also broadly dispersed across state and government.